Mesenteric panniculitis patients requiring emergency surgery: Report of three cases - Mustafa DUMAN,; Osman KOÇAK,; Olgaç FAZLI,; Cengiz KOÇAK,; Ali Emre ATICI,; Uğur DUMAN, (Turkish Journal of Gastroenterology, 2019)
-